2021
DOI: 10.3390/brainsci11081077
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers in Febrile Seizure: A Comprehensive Bibliometric, Review and Visualization Analysis

Abstract: Background: Inflammatory markers association with many diseases is the subject of many articles and reviews. This study presents a comprehensive bibliometric review and visualization analysis of inflammatory biomarkers (IB) in the context of febrile seizure (FS) patients. Methods: The study focused on IB in FS using (1) bibliometric analysis specific indicators and maps in order to analyze and present the network of authors, journals, universities, and countries, and (2) automated literature screening and unsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…We used the VOSviewer science visualization software package developed by Van Eck and Waltman at the Center for Science and Technology Studies of Leiden University [ 9 , 10 ]. The bibliometric approach using this tool was applied in studies from various areas of research [ 11 , 12 , 13 , 14 ]. We performed the following types of bibliographic techniques: citation analysis, co-word analysis, and co-citation analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We used the VOSviewer science visualization software package developed by Van Eck and Waltman at the Center for Science and Technology Studies of Leiden University [ 9 , 10 ]. The bibliometric approach using this tool was applied in studies from various areas of research [ 11 , 12 , 13 , 14 ]. We performed the following types of bibliographic techniques: citation analysis, co-word analysis, and co-citation analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to IL-1β and HMGB1, in ammatory cytokines, including IL-6 and TNF-α, might also have facilitatory effect on the development of FS [43]. IL-1β can binds to IL-1 receptor type 1 (IL-1R1), a toll receptor family member, and induces the transcription of various genes that encode several downstream mediators of in ammation, including TNF-a and IL-6, via an NF-κB pathway [31,44].…”
Section: Discussionmentioning
confidence: 99%
“…is the main cause of children's febrile convulsion [9], In many studies, it has been found that the cerebrospinal uid IL-1 β The level and serum IL-6 level are related to the increased risk of FSs in children [22]. Therefore, after virus infection, immune cells represented by neutrophils and lymphocytes participate in the body's immune response to the virus, and the secretion of corresponding cytokines is unbalanced, that is, the key leukocyte factor, such as IL-1, that promotes the onset of febrile convulsion β HMGB1 IL-6 TNF-α And key cytokines that inhibit the onset of febrile convulsion, such as IL-10, IL-1 receptor antagonist (IL-1RA), INF-β Steady state imbalance between, causing FS [19,23]. IgA receptor Fc present on eosinophils α, when bacteria and viruses are adhered to by IgA in respiratory mucosa or skin mucosa, they can activate the immune response of eosinophils, thus inducing degranulation of eosinophils [24].…”
Section: Disscusionmentioning
confidence: 99%